2014
DOI: 10.1111/anae.12933
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intra-operative transcutaneous electrical nerve stimulation on posterior neck pain following thyroidectomy

Abstract: SummaryPosterior neck pain following thyroidectomy is common because full neck extension is required during the procedure. We evaluated the effect of intra-operative transcutaneous electrical nerve stimulation on postoperative neck pain in patients undergoing total thyroidectomy under general anaesthesia. One hundred patients were randomly assigned to one of two groups; 50 patients received transcutaneous electrical nerve stimulation applied to the trapezius muscle and 50 patients acted as controls. Postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
0
19
1
Order By: Relevance
“…Transcutaneous electrical nerve stimulation (TENS) is a noninvasive form of neuromodulation that has demonstrated effectiveness in numerous pain conditions (13)(14)(15)(16). Specifically, peripheral stimulation including TENS has established utility in alleviating multiple oral and facial pain conditions (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Transcutaneous electrical nerve stimulation (TENS) is a noninvasive form of neuromodulation that has demonstrated effectiveness in numerous pain conditions (13)(14)(15)(16). Specifically, peripheral stimulation including TENS has established utility in alleviating multiple oral and facial pain conditions (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is debatable, some researchers have demonstrated that TENS has a placebo effect in reducing the overall pain intensity by about 20% to 30%. [30,31] Moreover, this study specifically blinded the patients to their treatment. The reason for which they were blinded is to lower their bias in favor of the CMT treatment, thus eliminating the placebo effect in the overall study.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, more than 80% of patients complain of posterior neck pain following thyroidectomy (Han et al, 2006). Thyroidectomy surgery is performed in the supine position while the patient's neck is placed at full extension (Park et al, 2015). Park et al (2015) suggested that this prolonged neck extension generates nociceptive stimuli and neural transmission intraoperatively, resulting in posterior neck pain following surgery.…”
mentioning
confidence: 99%
“…Thyroidectomy surgery is performed in the supine position while the patient's neck is placed at full extension (Park et al, 2015). Park et al (2015) suggested that this prolonged neck extension generates nociceptive stimuli and neural transmission intraoperatively, resulting in posterior neck pain following surgery. Moreover, muscle strain, ischaemia, anterior longitudinal ligament injury and hyperextension of cervical facet joints could contribute to neck pain development (Park et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation